2011
DOI: 10.1080/01431161.2011.608089
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal pattern validation of chlorophyll-a concentrations in Lake Okeechobee, Florida, using a comparative MODIS image mining approach

Abstract: A comparative analysis was conducted using three types of data-mining models produced from Moderate Resolution Imaging Spectroradiometer (MODIS) Terra Surface Reflectance 1-day or 8-day composite images to estimate chlorophyll-a (chl-a) concentrations in Lake Okeechobee, Florida. To understand the pros and cons of these three models, a genetic programming (GP) model was compared to an artificial neural network (ANN) model and multiple linear regression (MLR) model with respect to two different data sets relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…SAV is an important habitat, providing refuge to juvenile fish and shellfish and providing a food source for fish and waterfowl. Consequently, the assessment of SAV provides a direct link between water quality (nutrients, chlorophyll a, and suspended sediments) (Chang et al 2012) and ecologically and economically important species. The extent of SAV in a water system varies directly with water clarity and inversely with water depth.…”
Section: Sav Model Algorithmmentioning
confidence: 99%
“…SAV is an important habitat, providing refuge to juvenile fish and shellfish and providing a food source for fish and waterfowl. Consequently, the assessment of SAV provides a direct link between water quality (nutrients, chlorophyll a, and suspended sediments) (Chang et al 2012) and ecologically and economically important species. The extent of SAV in a water system varies directly with water clarity and inversely with water depth.…”
Section: Sav Model Algorithmmentioning
confidence: 99%
“…However, our approach showed an improvement over previously published models (e.g., CHANG et al, 2012;OGASHAWARA et al, 2014;WU et al, 2009) due to the implementation of search criteria based on a sequential automatic search of exclusion-inclusion algorithms for selecting parameters. In addition, the estimation of Chl-a concentrations based on MLR presented advantages (e.g., few input variables and explicit calculation of the coefficients of selected independent variables) in comparison with the ANN and NPMR models, which is difficult to interpret the relationship between input and output variables ("blackbox" models) (WU et al, 2014).…”
Section: Performance Of Chl-a Algorithmsmentioning
confidence: 78%
“…Recent studies have applied empirical algorithms for retrieving Chl-a concentrations in lakes and reservoirs combining MODIS spectral bands (DUAN et al, 2017;CHANG et al, 2012;HUANG et al, 2014;SHI et al, 2017;TANG, 2011;WU et al, 2009;XIANG et al, 2015;ZHANG et al, 2016). However, these algorithms were developed for eutrophics waters (e.g., Lakes Taihu and Chaohu, China and Lake Okeechobee, USA) and for particular seasons, limiting their uses elsewhere and throughout the year (MATTHEWS, 2011;PALMER et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the OC2 algorithm was first developed for SeaWiFSdata (Darecki and Stramski, 2004;O'Reilly et al, 1998;O'Reilly et al, 2000), it has proven to work in MODIS high resolution bands (500 m) in turbid waters (Hudson et al, 2000;Wang and Shi, 2008;Wang et al, 2007). OC2 algorithm has also been tested in turbid lake environments (Chang et al, 2012;Weghorst, 2008). Other studies have found the MODIS medium-resolution bands (250 and 500 m) to be 4 to5 times more sensitive than the Landsat 7 bands (Hu et al, 2004).…”
Section: Modis Datamentioning
confidence: 99%